AquaTrainer® snorkel does not increase hydrodynamic drag but influences turning time - Ribeiro, J.; Figueiredo, P.; Guidetti, L.; Alves, F.; Toussaint, H.; Vilas-Boas, J. P.; Baldari, C.; Fernandes, R. J. (International Journal of Sports Medicine, 2016)
Our purpose was to verify if the use of the new AquaTrainer® respiratory snorkel lead to an increase of front crawl hydrodynamic drag and whether the constraint of using an adapted turning technique influences its corresponding turning time. 12 swimmers performed 2 (without and with snorkel) 12×25 front crawl repetitions from low to maximal velocity on the measuring active drag system. Complementarily, 3 swimming turns were compared: open turn with snorkel, tumble turn and open turn without snorkel. Drag values were similar without vs. with snorkel at 0.9, 1.1, 1.3, 1.5 and 1.7?m.s-1 velocities: 15.84?±5.32 vs. 16.18±4.81, 25.60±6.69 vs. 26.03±6.17, 38.37±8.04 vs. 38.88±7.56, 54.64±10.06 vs. 55.08±9.55, 74.77±14.09 vs. 74.92±13.14 N, (respectively, p=0.05), and high agreement between conditions was observed (p<0.01). Front crawl swimming with snorkel using the open turn implied an increase in turning time of 14.2 and 5.1% than the tumble turn and open turn without the apparatus (p<0.01). AquaTrainer® snorkel does not lead to an increase in active drag during front crawl performed at a large range of velocities and, consequently, the metabolic energy necessary to overcome total drag will not be affected. However, turning with it requires an additional time that should be taken into account in scientific research and training conditions.